In the given table, we can see how the values of \(3^n\) change as the exponent \(n\) decreases. The pattern is that each time the exponent decreases by 1, the value is divided by 3:
- Starting from \(3^3\) (which equals 27) and moving down:
- \(3^2 = 27 / 3 = 9\)
- \(3^1 = 9 / 3 = 3\)
- \(3^0 = 3 / 3 = 1\) (thus \(a = 1\))
- \(3^{-1} = 1 / 3 = \frac{1}{3}\) (thus \(b = \frac{1}{3}\))
- \(3^{-2} = 1/9\) (already provided)
- \(3^{-3} = 1 / 27\) (thus \(c = \frac{1}{27}\))
From this, we find the values for the variables:
- \(a = 1\)
- \(b = \frac{1}{3}\)
- \(c = \frac{1}{27}\)
Here are the answers:
a = 1
b = \(\frac{1}{3}\)
c = \(\frac{1}{27}\)